Предмет:
АлгебраАвтор:
candiceopvxАвтор:
luna57Автор:
luluppubАвтор:
leajvr3Автор:
jaysonhaynesАвтор:
cameronenav1) =sin(α/2)*ctg(α/4)-cos(α/2)=sin(α/2)*((1+cos(α/2)/sin(α/2))-cos(α/2)=
1+cos(α/2)-cos(α/2)=1
2)=-cos(α/2)*(sin(α/2)/(1-cos(α/2))-sin(α/2)=(-sin(α/2)*cos(α/2)-sin(α/2)+sin(α/2)*cos(α/2))/(cos(1-α/2))=sin(α/2)/(cos(α/2)-1)
Автор:
natalietaylorДобавить свой ответ
Предмет:
ИсторияАвтор:
mckenzie57Ответов:
Смотреть
Предмет:
АлгебраАвтор:
brandiv82iОтветов:
Смотреть
Предмет:
Қазақ тiлiАвтор:
baby makergkygОтветов:
Смотреть
Предмет:
Русский языкАвтор:
daisycxtrОтветов:
Смотреть